TEPUNG KIAMBANG (Salvinia molesta) TERFERMENTASI SEBAGAI BAHAN PAKAN IKAN NILA (Oreochromis niloticus) - Warasto .; Yulisman .; Mirna Fitrani (Jurnal Akuakultur Rawa Indonesia, 2013)
The aims of this research was to examined the effect of fermented giant salvinia meal as feed ingrediant on growth, spesific growth rate, feed efficiency, and survival rate of tilapia. Research used completely randomized design with five treatments and three replications. The treatments were treatment with out used giant salvinia meal, and using 10%, 20%, 30%, and 40% fermented giant salvinia meal in feed formulation. Results showed that the using 10% fermented giant salvinia meal in feed formulation provided the best result were weight growth 2.28 g, specific growth rate 1.45%, feed efficiency 69.54%, and survival rate 98.33%. As long the research, water quality was in optimum  range for tilapia were  temperature 25-290C,  dissolved oxygen 5.60- 7.95 mg.L-1, pH 6.6-7.1, and amonia 0.009-0.016 mg.L-1.   Keywords: Giant salvinia, fermentation, feed efficiency, tilapia